MnFe2O4 / GO wave-absorbing aerogel with directional aperture structure and preparation method of MnFe2O4 / GO wave-absorbing aerogel

By preparing MnFe2O4/GO aerogel, the problems of impedance mismatch of graphene materials and high manganese ferrite density are solved, and the lightweight and wide-band strong wave absorption performance is achieved, which is suitable for microwave absorption materials.

CN120364757AActive Publication Date: 2025-07-25CENT SOUTH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510506122.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-07-25
Estimated Expiration
2045-04-22

AI Technical Summary

Technical Problem

The existing graphene materials have impedance mismatch and a single dissipation mechanism problems in electromagnetic wave absorbing materials, which are difficult to meet the comprehensive requirements of lightweight, thin, wide and strong. Traditional manganese ferrite materials have high density and are difficult to meet the requirements of lightweight.

Method used

By compounding manganese ferrite with graphene, a MnFe2O4/GO aerogel with a directional pore size structure is prepared, and a three-dimensional loose porous structure is formed by using the synergistic effect of dielectric loss and magnetic loss and multiple interface polarization.

Benefits of technology

It achieves a lightweight microwave absorption effect with wide wave absorbing frequency bandwidth and strong wave absorbing ability, meets the comprehensive requirements of new wave absorbing materials, and has good microwave absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120364757A_ABST
    Figure CN120364757A_ABST
Patent Text Reader

Abstract

The invention discloses MnFe2O4 / GO wave-absorbing aerogel with a directional aperture structure and a preparation method of the MnFe2O4 / GO wave-absorbing aerogel, and belongs to the technical field of preparation of wave-absorbing materials, manganese ferrite (MnFe2O4) magnetic particles are uniformly loaded on the surface of graphene, and graphene aerogel assembled by the magnetic particles with a three-dimensional loose porous structure is obtained; mnFe2O4 is prepared by adopting a low-temperature coprecipitation method, the MnFe2O4 / GO wave-absorbing aerogel is prepared by combining directional freezing and heat treatment, and the method is mild and simple. By introducing the manganese ferrite, the impedance imbalance problem of the graphene material is improved, the magnetic loss of the material is enhanced, and the novel porous aerogel wave-absorbing material with dielectric loss and magnetic loss is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of microwave absorbing materials, and particularly to a MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure and a preparation method thereof. Background Art

[0002] With the development of 5G communication technology, aerospace industry and anti-reconnaissance technology in the military field, people's attention has been increasingly focused on electromagnetic microwave absorbing materials, and the requirements for microwave absorbing materials have been continuously improved. Developing new electromagnetic wave absorbing materials with lightweight, thin thickness, wide absorption bandwidth and strong microwave absorbing performance has become an inevitable trend at present. Graphene, due to its light weight, unique two-dimensional structure and controllable dielectric properties, has been widely studied as an ideal candidate material for efficient microwave absorption. However, due to the too high conductivity of pure graphene materials, it is easy to cause impedance mismatch and single dissipation mechanism problems. When used as an electromagnetic microwave absorbing material, its performance in absorbing electromagnetic waves is not satisfactory, and it is difficult to meet the comprehensive requirements of the new generation of microwave absorbing materials for "thin, light, wide and strong", which greatly hinders its practical application in the field of electromagnetic wave absorption.

[0003] Spinel-type manganese ferrite (MnFe2O4) is an important ferrite. Due to its simple synthesis, low cost, excellent chemical stability, excellent magnetic loss characteristics and medium saturation magnetization intensity, it has always been used in the field of microwave absorption technology. It is known that multi-component design can optimize the electromagnetic attenuation characteristics of composite materials. Compared with solid microwave absorbing materials, aerogel materials have a more uniform pore distribution and lower density inside, and have a smaller effective dielectric constant, so they can achieve good matching of incident electromagnetic waves in a wide frequency range. However, its traditional bulk materials have a higher density and are difficult to meet the lightweight requirements.

[0004] In summary, there is an urgent need in this field to develop a new type of microwave absorbing material with lightweight, strong microwave absorbing ability and wide microwave absorption bandwidth and having a directional pore structure. By attempting to utilize the synergistic effect between dielectric loss and magnetic loss, as well as multiple interfacial polarizations between graphene and MnFe2O4, graphene with dielectric properties is compounded with magnetic manganese ferrite, and it is designed to be prepared into a MnFe2O4 / GO aerogel with a directional pore structure, so as to achieve the effect of enhancing microwave absorption and obtain a new type of microwave absorbing material with better microwave absorption performance. Summary of the Invention

[0005] The purpose of the present invention is to provide a MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure and a preparation method thereof. By compounding graphene and manganese ferrite, an aerogel with a directional pore structure is obtained under certain conditions, which has the advantages of lightweight, wide microwave absorption bandwidth, strong microwave absorbing ability, high porosity and simple preparation method.

[0006] To achieve the above object, the present invention provides a method for preparing a MnFe2O4 / GO absorbing aerogel with a directional pore structure, specifically including the following preparation steps:

[0007] 1) Weigh appropriate amounts of FeCl3·6H2O and MnCl2·4H2O, and dissolve them separately in deionized water to obtain an FeCl3 solution and a MnCl2 solution; weigh an appropriate amount of polyethylene glycol and dissolve it in deionized water to obtain solution A;

[0008] 2) Mix the FeCl3 solution and the MnCl2 solution obtained in step 1) evenly in a three-necked flask with a small amount of dilute sulfuric acid added;

[0009] 3) Place the three-necked flask in a water bath, add solution A, stir at an appropriate temperature, add a sodium hydroxide solution to adjust the pH and then let it react fully to obtain solution B;

[0010] 4) Wash the solution B obtained in step 3) repeatedly with deionized water until the pH is neutral to obtain solution C;

[0011] 5) Weigh an appropriate amount of graphene oxide, dissolve it in deionized water and perform ultrasonic treatment, and then stir fully to obtain a brownish-yellow graphene oxide solution;

[0012] 6) Mix the solution C obtained in step 4) and the graphene oxide solution obtained in step 5) according to a certain volume ratio, and stir at room temperature for 8 - 18 h to obtain solution D;

[0013] 7) Perform directional freezing and drying treatments on the solution D obtained in step 6);

[0014] 8) Place the MnFe2O4 / GO aerogel obtained in step 7) in a tubular furnace and perform heat treatment under an atmosphere protection to obtain the MnFe2O4 / GO aerogel.

[0015] Preferably, in the above method for preparing a MnFe2O4 / GO absorbing aerogel with a directional pore structure, the molar ratio of FeCl3·6H2O to deionized water in step 1) is 1 - 6:9 - 20, the molar ratio of MnCl2·4H2O to deionized water is 1 - 5:18 - 45, and the mass ratio of polyethylene glycol to deionized water is 3 - 8:100.

[0016] Preferably, in the above method for preparing a MnFe2O4 / GO absorbing aerogel with a directional pore structure, the reaction temperature in step 3) is 60 - 100 °C, the stirring time is 10 - 60 min, the reaction time is 1 - 5 h, and the pH is greater than 11.

[0017] Preferably, in the above preparation method of the MnFe₂O₄ / GO microwave-absorbing aerogel with a directional pore structure, the volume of solution C in step 4) is controlled to be 100-400 ml.

[0018] Preferably, in the above preparation method of the MnFe₂O₄ / GO microwave-absorbing aerogel with a directional pore structure, the mass ratio of graphene oxide to deionized water in step 5) is 1-10:100.

[0019] Preferably, in the above preparation method of the MnFe₂O₄ / GO microwave-absorbing aerogel with a directional pore structure, the mass ratio of manganese ferrite in solution C to graphene in the graphene oxide solution in step 6) is 1-8:4-12.

[0020] Preferably, in the above preparation method of the MnFe₂O₄ / GO microwave-absorbing aerogel with a directional pore structure, the freezing temperature in step 7) is -20 to -90 °C, the time is 12-24 h, and the drying time is 12-72 h.

[0021] Preferably, in the above preparation method of the MnFe₂O₄ / GO microwave-absorbing aerogel with a directional pore structure, the protective atmosphere in step 8) is one of nitrogen and argon, the heating rate of heat treatment is 1-15 °C / min, the holding temperature is 200-700 °C, and the holding time is 1-6 h.

[0022] The MnFe₂O₄ / GO microwave-absorbing aerogel with a directional pore structure obtained by the above preparation method has magnetic particles MnFe₂O₄ uniformly loaded on the surface of graphene, and the obtained graphene aerogel has a three-dimensional porous structure.

[0023] Therefore, the present invention adopts the MnFe₂O₄ / GO microwave-absorbing aerogel with a directional pore structure and its preparation method with the above structure. The obtained aerogel includes graphene with a connected directional honeycomb pore structure. The unique wrinkles on the surface of the top layer of graphene are clearly visible, and microspherical manganese ferrite is distributed on the surface of layered graphene. This aerogel has the characteristics of extremely light weight and can be easily supported by grass. Through the synergistic effect between dielectric loss and magnetic loss, as well as multiple interfacial polarizations between graphene and MnFe₂O₄, the effect of enhancing its microwave absorption is achieved.

[0024] The technical solution of the present invention will be further described in detail below with reference to the drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a diagram of the directional freezing process of the MnFe₂O₄ / GO aerogel in Example 1.

[0026] Figure 2 Absorbing wave performance diagram of the MnFe2O4 / GO aerogel sample of Example 1.

[0027] Figure 3 SEM diagram of the MnFe2O4 / GO absorbing wave aerogel sample of Example 1.

[0028] Figure 4 Absorbing wave performance diagram of the MnFe2O4 / GO aerogel sample of Example 2.

[0029] Figure 5 SEM diagram of the MnFe2O4 / GO absorbing wave aerogel sample of Example 2.

[0030] Figure 6 Absorbing wave performance diagram of the MnFe2O4 / GO aerogel sample of Example 3.

[0031] Figure 7 SEM diagram of the MnFe2O4 / GO absorbing wave aerogel sample of Example 3. Detailed implementation manners

[0032] In order to better understand the above technical solutions, the following will describe the above technical solutions in detail in conjunction with the accompanying drawings of the specification and specific implementation manners. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0033] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "the" and "said" used in the embodiments of the present invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise. "Plural" generally includes at least two.

[0034] It should also be noted that the term "comprising", "including" or any other variant thereof is intended to cover a non-exclusive inclusion, so that a commodity or device including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or further includes elements inherent to such commodity or device. Without further limitation, the element defined by the statement "including one..." does not exclude the existence of another identical element in the commodity or device including the said element.

[0035] The present invention provides a preparation method of MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure, in which magnetic particles MnFe2O4 are uniformly loaded on the surface of graphene to obtain a graphene aerogel assembled by magnetic particles with a three-dimensional loose porous structure;

[0036] Specifically, it includes the following preparation steps:

[0037] 1) Weigh appropriate amounts of FeCl3·6H2O and MnCl2·4H2O, and dissolve them separately in deionized water to obtain an FeCl3 solution and an MnCl2 solution; weigh an appropriate amount of polyethylene glycol and dissolve it in deionized water to obtain solution A;

[0038] 2) Mix the FeCl3 solution and the MnCl2 solution obtained in step 1) evenly in a three-necked flask with a small amount of dilute sulfuric acid added;

[0039] 3) Place the three-necked flask in a water bath, add solution A, stir at an appropriate temperature, add sodium hydroxide solution to adjust the pH, and then let it react fully to obtain solution B;

[0040] 4) Wash the solution B obtained in step 3) repeatedly with deionized water until the pH is neutral to obtain solution C;

[0041] 5) Weigh an appropriate amount of graphene oxide, dissolve it in deionized water, perform ultrasonic treatment, and then stir it fully to obtain a brownish-yellow graphene oxide solution;

[0042] 6) Mix the solution C obtained in step 4) and the graphene oxide solution obtained in step 5) according to a certain volume ratio, stir at room temperature for 8 - 18 h to obtain solution D;

[0043] 7) Perform directional freezing and drying treatment on the solution D obtained in step 6);

[0044] 8) Put the MnFe2O4 / GO aerogel obtained in step 7) into a tube furnace, and perform heat treatment under an atmosphere protection to obtain the MnFe2O4 / GO aerogel.

[0045] To further optimize the above technical solution, in step 1), the molar ratio of FeCl3·6H2O to deionized water is 1 - 6:9 - 20, the molar ratio of MnCl2·4H2O to deionized water is 1 - 5:18 - 45, and the mass ratio of polyethylene glycol to deionized water is 3 - 8:100.

[0046] To further optimize the above technical solution, in step 3), the reaction temperature is 60 - 100 °C, the stirring time is 10 - 60 min, the reaction time is 1 - 5 h, and the pH is greater than 11.

[0047] To further optimize the above technical solution, in step 4), the volume of solution C is controlled to be 100 - 400 ml.

[0048] To further optimize the above technical solution, in step 5), the mass ratio of graphene oxide to deionized water is 1 - 10:100.

[0049] To further optimize the above technical solution, in step 6), the mass ratio of manganese ferrite in solution C to graphene in the graphene oxide solution is 1 - 8:4 - 12.

[0050] To further optimize the above technical solution, in step 7), the freezing temperature is -20 - -90 °C, the time is 12 - 24 h, and the drying time is 12 - 72 h.

[0051] To further optimize the above technical solution, in step 8), the protective atmosphere is one of nitrogen and argon, the heating rate of the heat treatment is 1 - 15 °C / min, the holding temperature is 200 - 700 °C, and the holding time is 1 - 6 h.

[0052] The MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure is obtained by the above - described preparation method. The magnetic particles MnFe2O4 are uniformly loaded on the surface of graphene, and the obtained graphene aerogel has a three - dimensional loose porous structure.

[0053] To introduce more clearly and in detail a MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure and its preparation method provided by the embodiments of the present invention, the following will be described in combination with specific embodiments.

[0054] Example 1

[0055] 1) Weigh 3.957 g of FeCl3·6H2O and dissolve it fully in 50 ml of deionized water. Weigh 3.957 g of MnCl2·4H2O and dissolve it fully in 25 ml of deionized water. Weigh 5 g of polyethylene glycol and dissolve it in 50 ml of deionized water to obtain solution A.

[0056] 2) Mix the FeCl3 solution and the MnCl2 solution obtained in step 1) evenly in a three - necked flask with a small amount of dilute sulfuric acid added.

[0057] 3) Place the three - necked flask in a water bath, add solution A, stir at 60 °C for a period of time, add sodium hydroxide solution to adjust the pH to 11 and then let it react for 2 h to obtain solution B.

[0058] 4) Wash the solution B obtained in step 3) repeatedly with deionized water until the pH is neutral to obtain solution C.

[0059] 5) Weigh 2 g of graphene oxide, dissolve it in 200 ml of deionized water, and perform ultrasonic treatment. Then, stir it thoroughly to obtain a brownish-yellow graphene oxide solution.

[0060] 6) Mix the solution C obtained in step 4) with the graphene solution obtained in step 5) at a volume ratio of 11:100, and stir at room temperature for 8 - 18 h to obtain solution D.

[0061] 7) Place the solution D obtained in step 6) under the condition of -20 to -90 °C for freezing for 12 - 24 h, and the drying time is 12 - 72 h.

[0062] 8) Put the MnFe2O4 / GO aerogel obtained in step 7) into a tubular furnace, and under the protection of a nitrogen atmosphere, perform heat treatment at 300 °C for 2 h to obtain the MnFe2O4 / GO aerogel.

[0063] Dope the obtained MnFe2O4 / GO aerogel with paraffin to prepare a coaxial ring sample (the inner diameter of the coaxial ring sample is 3 mm and the outer diameter is 7 mm). Measure the electromagnetic parameters of the sample through a vector network analyzer, and then calculate the wave absorption performance of the material through CST STUDIO SUITE software. The wave absorption performance of the obtained MnFe2O4 / GO wave-absorbing aerogel is as Figure 2 shown. It can be seen from the figure that when the material thickness is 2.9 mm, the minimum reflection loss at 9.46 GHz reaches -29.24 dB. At this time, the widest effective absorption frequency band reaches 4.72 GHz, having effective wave absorption performance. The SEM image of the obtained MnFe2O4 / GO wave-absorbing aerogel sample is as Figure 3 shown.

[0064] Example 2

[0065] 1) Weigh 3.957 g of FeCl3·6H2O and dissolve it thoroughly in 50 ml of deionized water. Weigh 3.957 g of MnCl2·4H2O and dissolve it thoroughly in 25 ml of deionized water. Weigh 5 g of polyethylene glycol and dissolve it in 50 ml of deionized water to obtain solution A.

[0066] 2) Mix the FeCl3 solution and the MnCl2 solution obtained in step 1) evenly in a three-necked flask with a small amount of dilute sulfuric acid added.

[0067] 3) Place the three-necked flask in a water bath, add solution A, stir at 60 °C for a period of time, add sodium hydroxide solution to adjust the pH to 11, and then let it react for 2 h to obtain solution B.

[0068] 4) Wash the solution B obtained in step 3) repeatedly with deionized water until the pH is neutral to obtain solution C.

[0069] 5) Weigh 2 g of graphene oxide, dissolve it in 200 ml of deionized water, and perform ultrasonic treatment. Then, stir it thoroughly for 8 - 18 h to obtain a brownish-yellow graphene oxide solution.

[0070] 6) Mix the solution C obtained in step 4) and the graphene solution obtained in step 5) at a volume ratio of 11:50, and stir for 12 h at room temperature to obtain solution D.

[0071] 7) Place the solution D obtained in step 6) in a freezer at -20 to -90 °C for 12 - 24 h, and the drying time is 12 - 72 h.

[0072] 8) Put the MnFe2O4 / GO aerogel obtained in step 7) into a tube furnace, and under the protection of a nitrogen atmosphere, perform heat treatment at 300 °C for 2 h to obtain the MnFe2O4 / GO aerogel.

[0073] Dope the obtained MnFe2O4 / GO aerogel with paraffin to prepare a coaxial ring sample (the inner diameter of the coaxial ring sample is 3 mm and the outer diameter is 7 mm). Measure the electromagnetic parameters of the sample through a vector network analyzer, and then calculate the wave absorption performance of the material through CST STUDIO SUITE software. The wave absorption performance of the prepared MnFe2O4 / GO wave-absorbing aerogel is as Figure 4 shown. It can be seen from the figure that when the material thickness is 4.9 mm, the minimum reflection loss at 9.01 GHz reaches -30.91 dB, and the widest effective absorption bandwidth at this time reaches 4.70 GHz, having effective wave absorption performance. The SEM image of the MnFe2O4 / GO wave-absorbing aerogel sample is as Figure 5 shown.

[0074] Example 3

[0075] 1) Weigh 3.957 g of FeCl3·6H2O and dissolve it fully in 50 ml of deionized water. Weigh 3.957 g of MnCl2·4H2O and dissolve it fully in 25 ml of deionized water. Weigh 5 g of polyethylene glycol and dissolve it in 50 ml of deionized water to obtain solution A.

[0076] 2) Mix the FeCl3 solution and the MnCl2 solution obtained in step 1) evenly in a three-necked flask with a small amount of dilute sulfuric acid added.

[0077] 3) Place the three-necked flask in a water bath, add solution A, stir for a period of time at 60 °C, add sodium hydroxide solution to adjust the pH to 11, and then let it react for 2 h to obtain solution B.

[0078] 4) Wash the solution B obtained in step 3) repeatedly with deionized water until the pH is neutral to obtain solution C.

[0079] 5) Weigh 2 g of graphene oxide, dissolve it in 200 ml of deionized water, perform ultrasonic treatment, and then stir it thoroughly to obtain a brownish-yellow graphene oxide solution.

[0080] 6) Mix the solution C obtained in step 4) with the graphene solution obtained in step 5) at a volume ratio of 22:50, and stir at room temperature for 8 - 18 h to obtain solution D.

[0081] 7) Place the solution D obtained in step 6) under freezing conditions of -20 °C to -90 °C for 12 - 24 h, and the drying time is 12 - 72 h.

[0082] 8) Put the MnFe2O4 / GO aerogel obtained in step 7) into a tubular furnace, and under the protection of a nitrogen atmosphere, perform heat treatment at 300 °C for 2 h to obtain the MnFe2O4 / GO aerogel.

[0083] Dope the obtained MnFe2O4 / GO aerogel with paraffin to prepare a coaxial ring sample (the inner diameter of the coaxial ring sample is 3 mm and the outer diameter is 7 mm). Measure the electromagnetic parameters of the sample through a vector network analyzer, and then calculate the wave absorption performance of the material through CST STUDIO SUITE software. The wave absorption performance of the obtained MnFe2O4 / GO wave-absorbing aerogel is as Figure 6 shown. It can be seen from the figure that when the material thickness is 2.8 mm, the minimum reflection loss reaches -54.98 dB at 16.43 GHz. At this time, the widest effective absorption bandwidth reaches 5.87 GHz, showing effective wave absorption performance. The SEM image of the MnFe2O4 / GO wave-absorbing aerogel sample is as Figure 7 shown.

[0084] It can be seen from Examples 1 - 3 that aerogels with different ratios all show significant wave absorption ability at specific frequencies, and the minimum reflection losses are all lower than -29 dB. Among them, the minimum reflection loss of Example 3 can reach -54.98 dB (16.43 GHz, thickness 2.8 mm), indicating that the material has a very strong attenuation ability for electromagnetic waves. The effective absorption bandwidths all exceed 4.7 GHz, and that of Example 3 can reach 5.87 GHz, covering a relatively wide microwave frequency band (such as X-band, Ku-band, etc.), meeting the requirements of broadband wave-absorbing materials.

[0085] By adjusting the volume ratio of the MnFe2O4 precursor solution (Solution C) to the graphene oxide solution (11:100 for Example 1, 11:50 for Example 2, and 22:50 for Example 3), key parameters affecting the wave absorption performance can be significantly influenced, including: the minimum absorption peak shifts from 9.46 GHz in Example 1, to 9.01 GHz in Example 2, and then to 16.43 GHz in Example 3, covering a range from low frequency to high frequency, indicating that the wave absorption frequency band can be regulated by adjusting the ratio. The thickness range is 2.8 - 4.9 mm, and Example 3 achieves a stronger wave absorption effect at a higher frequency with a relatively thin thickness (2.8 mm), demonstrating the advantage of the material being lightweight and thin.

[0086] SEM images ( Figure 3 、 5 、7) show that the aerogels with different ratios have specific microstructures, which may be porous networks or layered composite structures. This structure is conducive to multiple scattering and loss of electromagnetic waves. Combining the magnetic loss of MnFe2O4 and the dielectric loss of graphene oxide forms a synergistic wave absorption effect.

[0087] The preparation process is achieved through a co-precipitation - freeze-drying - heat treatment process. The steps have strong repeatability, and coaxial ring samples are made by doping paraffin, proving that the material can be compounded and processed with the matrix and is suitable for the preparation of actual devices. Heat treatment at 300 °C in a nitrogen atmosphere ensures the structural stability of the material, avoids oxidation, and guarantees the reliability of the wave absorption performance.

[0088] The MnFe2O4 / GO aerogel realizes excellent wave absorption performance with low reflection loss, wide effective absorption bandwidth, and adjustable thickness by regulating the composite ratio of MnFe2O4 and graphene oxide, and has significant application potential in the field of microwave absorption (such as stealth materials, electromagnetic interference shielding, etc.). Among them, the ratio of Example 3 (volume ratio 22:50) shows the optimal performance, with both high attenuation ability and broadband characteristics, providing a direction for further optimization of the material.

[0089] Therefore, the present invention adopts a MnFe2O4 / GO wave-absorbing aerogel with a directional pore structure and its preparation method with the above structure. The obtained aerogel includes graphene with an interconnected directional honeycomb pore structure, and distinct wrinkles on the surface of the top-layer graphene are clearly visible. Microspherical manganese ferrite is distributed on the surface of the layered graphene. This aerogel has an extremely lightweight characteristic and can be easily supported by grass. Through the synergistic effect between dielectric loss and magnetic loss, as well as multiple interfacial polarizations between graphene and MnFe2O4, the microwave absorption effect is enhanced.

[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions of the present invention or make equivalent replacements, and these modifications or equivalent replacements cannot make the modified technical solutions deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A preparation method of MnFe2O4 / GO microwave absorption aerogel with a directional pore structure, characterized in that, Specifically, it includes the following preparation steps: 1) Weigh appropriate amounts of FeCl3·6H2O and MnCl2·4H2O, and dissolve them in deionized water respectively to obtain an FeCl3 solution and an MnCl2 solution; weigh an appropriate amount of polyethylene glycol and dissolve it in deionized water to obtain solution A; 2) Mix the FeCl3 solution and the MnCl2 solution obtained in step 1) evenly in a three-necked flask with a small amount of dilute sulfuric acid added; 3) Place the three-necked flask in a water bath, add solution A, stir at an appropriate temperature, add sodium hydroxide solution to adjust the pH and then let it react fully to obtain solution B; 4) Wash the solution B obtained in step 3) repeatedly with deionized water until the pH is neutral to obtain solution C; 5) Weigh an appropriate amount of graphene oxide, dissolve it in deionized water and perform ultrasonic treatment, and then stir it fully to obtain a brownish-yellow graphene oxide solution; 6) Mix the solution C obtained in step 4) and the graphene oxide solution obtained in step 5) according to a certain volume ratio, and stir at room temperature for 8 - 18 h to obtain solution D; 7) Perform directional freezing and drying treatments on the solution D obtained in step 6); 8) Put the MnFe2O4 / GO aerogel obtained in step 7) into a tube furnace, and perform heat treatment under an atmosphere protection to obtain the MnFe2O4 / GO aerogel.

2. The preparation method of a MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure according to claim 1, characterized in that, In step 1), the molar ratio of FeCl3·6H2O to deionized water is 1 - 6:9 - 20, the molar ratio of MnCl2·4H2O to deionized water is 1 - 5:18 - 45, and the mass ratio of polyethylene glycol to deionized water is 3 - 8:

100.

3. The preparation method of an MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure according to claim 1, characterized in that, In step 3), the reaction temperature is 60 - 100 °C, the stirring time is 10 - 60 min, the reaction time is 1 - 5 h, and the pH is greater than 11.

4. The preparation method of a MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure according to claim 1, characterized in that, In step 4), control the volume of solution C to be 100 - 400 ml.

5. The preparation method of a MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure according to claim 1, characterized in that, In step 5), the mass ratio of graphene oxide to deionized water is 1 - 10:

100.

6. The preparation method of an MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure according to claim 1, characterized in that, In step 6), the mass ratio of the manganese ferrite in solution C to the graphene in the graphene oxide solution is 1 - 8:4 - 12; 7. The preparation method of a MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure according to claim 1, characterized in that, In step 7), the freezing temperature is -20 - -90 °C, the time is 12 - 24 h, and the drying time is 12 - 72 h.

8. The preparation method of a MnFe₂O₄ / GO microwave absorption aerogel with a directional pore structure according to claim 1, characterized in that, In step 8), the protective atmosphere is one of nitrogen and argon, the heating rate of the heat treatment is 1 - 15 °C / min, the holding temperature is 200 - 700 °C, and the holding time is 1 - 6 h.

9. The MnFe2O4 / GO microwave absorbing aerogel with a directional pore structure obtained by the preparation method according to any one of claims 1 to 8, characterized in that, Magnetic particles MnFe2O4 are evenly loaded on the surface of graphene, and the obtained graphene aerogel has a three-dimensional loose porous structure.

Citation Information

Patent Citations

  • Method for preparing nanometer MnFe2O4 / graphene composite material

    CN104944474A

  • Preparation method of reduced graphene oxide / manganese ferrite nano-composite wave absorbing material

    CN108559445A

  • MOFs (Metal-Organic Frameworks) derived carbon coated ferrite wave-absorbing material as well as preparation method and application thereof

    CN114498068A

  • Three-dimensional oriented porous aerogel loaded with hollow oxide nano box as well as preparation method and application of three-dimensional oriented porous aerogel

    CN115594232A

  • Anisotropic multifunctional carbon-based wave-absorbing aerogel as well as preparation method and application thereof

    CN118929648A